Evaluating methods of eliciting language production data ininterlanguage pragmatic research - Taw, Ly Wen; Chan, Swee Heng; Rafik-Galea, Shameem (Universiti Putra Malaysia Press, 2014)
Interlanguage Pragmatics (ILP) research methods are divided into production-based methods and perception-based methods. This paper focuses on production-based methods giving a variety of possibilities for the elicitation of pragmatic language data. Eight methods are reviewed in this paper including the methods which are commonly used in ILP studies such as discourse completion tasks (DCT) and role play. It also reviews the innovative methods like Multimedia Elicitation Task (MET) and Naturalised Role Play (NRP) which are newly developed for pragmatic studies. The design methods range from those that use highly controlled approaches to those that have no deliberate constraints. The advantages and disadvantages of each method are explained and discussed. The paper concludes with a note on the researchers’ decision on an appropriate method in ILP research which depends on various factors such as degree of authenticity, ease of administration, sample size, and research goal.